Residential segregation and overall survival of women with epithelial ovarian cancer. Issue 16 (2nd June 2020) - Westrick, Ashly C.; Bailey, Zinzi D.; Schlumbrecht, Matthew; Hlaing, WayWay M.; Kobetz, Erin E.; Feaster, Daniel J.; Balise, Raymond R.
Abstract : Background: To the authors' knowledge, the etiology of survival disparities in patients with epithelial ovarian cancer (EOC) is not fully understood. Residential segregation, both economic and racial, remains a problem within the United States. The objective of the current study was to analyze the effect of residential segregation as measured by the Index of Concentration at the Extremes (ICE) on EOC survival in Florida by race and/or ethnicity. Methods: All malignant EOC cases were identified from 2001 through 2015 using the Florida Cancer Data System (FCDS). Census‐defined places were used as proxies for neighborhoods. Using 5‐year estimates from the American Community Survey, 5 ICE variables were computed: economic (high vs low), race and/or ethnicity (non‐Hispanic white [NHW] vs non‐Hispanic black [NHB] and NHW vs Hispanic), and racialized economic segregation (low‐income NHB vs high‐income NHW and low‐income Hispanic vs high‐income NHW). Random effects frailty models were conducted. Results: A total of 16, 431 malignant EOC cases were diagnosed in Florida among women living in an assigned census‐defined place within the time period. The authors found that economic and racialized economic residential segregations influenced EOC survival more than race and/or ethnic segregation alone in both NHB and Hispanic women. NHB women continued to have an increased hazard of death compared with NHW women after controlling for multiple covariates, whereas Hispanic women were found to have either a similar or decreased hazard of death compared with NHW women in multivariable Cox models. Conclusions: The results of the current study indicated that racial and economic residential segregation influences survival among patients with EOC. Research is needed to develop more robust segregation measures that capture the complexities of neighborhoods to fully understand the survival disparities in EOC. Abstract : The authors report that racial and economic residential segregation influences survival among women with epithelial ovarian cancer (EOC). Research is needed to develop more robust segregation measures that capture the complexities of neighborhoods to fully understand the survival disparity among women with EOC.